A computational investigation of the selectivity and mechanism of the Lewis acid catalyzed oxa-Diels-Alder cycloaddition of substituted diene with benzaldehyde - Khorief Nacereddine, Abdelmalek (Journal of computational chemistry, 2021)
© 2021 Wiley Periodicals LLC.